(untitled) (REVISTA SAYWA, 2020)
Agrobacterium tumefaciens is a plant pathogenic bacterium that causes disease by introducing genes into plant cells. This ability of Agrobacterium has been exploited in biotechnology to introduce genes of interest and express them in plant cells. Gene expression in plant cells can be either transient or stable. The implementation of transient gene expression has made it possible to understand, among many other things, the molecular strategies used by plant cells to recognize invading pathogens. For this reason, the research groups Ciencias Biológicas y Químicas at Universidad Antonio Nariño and Manihot Biotec at Universidad Nacional de Colombia have focused on expressing disease resistance proteins of cassava that confer resistance to the bacterium Xanthomonas axonopodis pv. manihotis in order to study the molecular mechanisms employed by cassava cells to recognize this bacterial pathogen.